The Factors that Affect Stroke at Young Age in Brawijaya Hospital Surabaya - Siti Alchuriyah; Chatarina Umbul Wahjuni (Universitas Airlangga, 2016)
Stroke is one of type of non-communicable disease (NCD), the number of sufferers continues to increase each year and can occur at young and old ages. This study aims to determine the risk factors that influence the incidence of stroke in young patients in Brawijaya Hospital Surabaya. This research use a case-control study design and retrospective approach. The data taken is secondary data from the 2012-2013 medical records. Variables include the age of stroke, gender, hypertension, obesity, cholesterol levels, diabetes mellitus. Case samples were all young stroke patients <50 years and control samples were stroke patients ≥ 50 years. The total number of samples is 60. Comparison of cases with controls 1: 3. The sampling technique in control cases is simple random sampling. Analyzes were performed using logistic regression tests for bivariate and multiple logistic regression tests for multivariate. Most respondents aged ≥ 50 years (75%), male (55%), have a history of hypertension (85%), are not obese (53.3%), have elevated cholesterol levels (58.3%), and has a history of diabetes mellitus (53.3%). Risk factors for obesity have a significant effect on the incidence of stroke at a young age (p = 0.015). Multivariate test results showed that someone with a Body Mass Index status between 30-39.99 (Obesity 2) has a significant influence on the incidence of stroke at a young age (p = 0.0033) The conclusion of the study is obesity is related to risk factors for young stroke events. Health workers are advised to routinely conduct counseling about risk factors for stroke at a young age.